Media in the Social and Cultural Upbringing of Society (Journal of Human Sciences, 2020)
The increasing spread of the media in its various forms has caused many individuals, institutions and countries to exploit it positively and sometimes negatively. This case has noticeable effect on the socialization of individuals or in various educational institutions. This research has sought to identify the role of the media in cultural and social formation in  Society. It discusses the seriousness of the misuse of the media, and identify  some of the negative and positive effects of different media on the behavior of individuals using the descriptive analytical approach. This research concluded that the media has an effective role in cultural and social formation among members of society if it is exploited in a positive way. It stresses that cultural and social awareness are important for family members and all young students from schools and universities, as it contributes to the progress of society culturally and socially. Media is the basis of social and cultural interaction.One of the important means of broadcasting  is the (TV and Radio) audio and video. This is because of its direct impact on the family in terms of psychological, social and cultural aspect. Almost all families follow many programs, especially those related to cultural and social life, and the interest of educational and educational institutions is in publishing purposeful and diversified books and newspapers among members of society. The youth also are encouraged to read and be informed in order to keep pace with technological, cultural, social and political developments that occur in all human societies.